Rapid Appraisal of the Postharvest Facilities Projects in the Philippines - Nerlita M. Manalili; Kevin F. Yaptenco; Alessandro A. Manilay (Philippine Institute for Development Studies (PIDS), 2015)
The Philippine government's postharvest loss reduction programs entail significant investments (manpower, facilities, and equipment) and their impacts need evaluating. Thus, the Philippine Institute for Development Studies and the National Economic and Development Authority commissioned NEXUS Agribusiness Solutions to undertake the "Rapid Appraisal of Selected Postharvest Facilities in the Philippines".The postharvest facilities (PHF) selection process considered at least one each for Luzon, Visayas, and Mindanao, and for the following PHF categories: 1. equipment and facilities required immediately after harvest; 2. processing and storage facilities; and 3. market infrastructure and transport facilities. Selected were four rice processing centers, established through a Korean International Cooperation Agency grant, in Pangasinan, Davao del Sur, Bohol, and Iloilo. Using these sites as hub, other nearby PHF such as food terminals, flatbed dryers, and threshers were included for evaluation.In the context of upgrading value chains, reducing postharvest losses and improving economic outcomes for smallholder farmers, selected PHF were characterized and assessed. Recommendations centered on project management enhancement (timeliness of preparatory activities, participatory planning, etc.) and on operational improvements (capacity utilization, viability, and sustainability).
Keywords: 330; Philippines; postharvest loss; postharvest facility; value chain; agricultural marketing; rapid appraisal